Constraints on Tone Sensitivity in Novel Word Learning by Monolingual and Bilingual Infants: Tone Properties Are More Influential than Tone Familiarity - Burnham, Denis; Singh, Leher; Mattock, Karen; Woo, Pei J.; Kalashnikova, Marina (Frontiers in Psychology, 2018)
This study compared tone sensitivity in monolingual and bilingual infants in a novel word learning task. Tone language learning infants (Experiment 1, Mandarin monolingual; Experiment 2, Mandarin-English bilingual) were tested with Mandarin (native) or Thai (non-native) lexical tone pairs which contrasted static vs. dynamic (high vs. rising) tones or dynamic vs. dynamic (rising vs. falling) tones. Non-tone language, English-learning infants (Experiment 3) were tested on English intonational contrasts or the Mandarin or Thai tone contrasts. Monolingual Mandarin language infants were able to bind tones to novel words for the Mandarin High-Rising contrast, but not for the Mandarin Rising-Falling contrast; and they were insensitive to both the High-Rising and the Rising-Falling tone contrasts in Thai. Bilingual English-Mandarin infants were similar to the Mandarin monolinguals in that they were sensitive to the Mandarin High-Rising contrast and not to the Mandarin Rising-Falling contrast. However, unlike the Mandarin monolinguals, they were also sensitive to the High Rising contrast in Thai. Monolingual English learning infants were insensitive to all three types of contrasts (Mandarin, Thai, English), although they did respond differentially to tone-bearing versus intonation-marked words. Findings suggest that infants’ sensitivity to tones in word learning contexts depends heavily on tone properties, and that this influence is, in some cases, stronger than effects of language familiarity. Moreover, bilingual infants demonstrated greater phonological flexibility in tone interpretation.